One more moment - Chase, Samantha (Chase, Samantha. Shaughnessy brothers, band on the run, 2018)
Julian Grayson is taking a break ... from his cheating fiancée ... from his band ... from his life in the spotlight. Charlotte Clark is devoted to her work ... to save the world ... to help the homeless ... to get a broken man back on his feet. When Charlotte Clark offers to pay for Julian Grayson's coffee, the world-famous drummer assumes she wants something from him. But Charlotte has no idea who he is, and Julian can't resist keeping up the charade--being incognito is a novelty and a relief. He'll have to tell her ... eventually. But as Charlotte cheerfully undertakes to transform his life, Julian realizes there's something about her that gives him what he hasn't felt in years: hope.--Provided by Publisher.